Development of HOTS (High Order Thinking Skill) Oriented Learning Through Discovery Learning Model to Increase The Critical Thinking Skill of High School Students - Purnama Indah (International Journal of Chemistry Education Research, 2020)
The aim of this research is to produce HOTS (High Order Thinking Skill) lesson through a valid, practical, and effective discovery learning model for class XI high schools to improve students' critical thinking skills. This research is a development that refers to the Borg & Gall model. The subject trials for grade XI students of SMA Negeri 2 Sangatta Utara, East Kutai. Validity and practicality analysis techniques used percentage of descriptive techniques. The effectiveness analysis technique is by looking at the percentage of increase in students' pretest-posttest results. The result of this research in the form of development of learning tools which included: Syllabus, teaching materials, LKPD, and assessment instruments. The result showed that learning tools that have been developed meet the validity with a validity percentage of 99.66% which is categorized as very valid. The practicality of the lesson plan produced is very practical, this is indicated by the assessment of students as research respondents about 85.93%. HOTS (High Order Thinking Skill) lesson plan through Discovery Learning model to improve student’s critical thinking skills that are produced are able to provide the effectiveness learning, it looked through an increased in learning between pretest and posttest about 33%.Keywords: development, lesson plan, HOTS (high order thinking skill), discovery learning model, students' critical thinking skill